2021
DOI: 10.1017/s0954102020000632
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of the species of notothenioid fishes

Abstract: We provide our perspective on the species-level taxonomy of notothenioid fishes, the dominant component of the fish fauna of Antarctica. There are 140 species in 45 genera, an increase of 15% since the previous summary in 2000. Biogeographically, 30 species are non-Antarctic, 33 are sub-Antarctic and 77 are Antarctic. The checklist is documented with footnotes that provide the rationale for our decisions. Supplementary Material provides additional details for our decisions on two species of Pogonophryne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
2
28
0
2
Order By: Relevance
“…2) differ by 421–540 substitutions and 25–34 indels (253–272 substitutions and 6–11 indels when the ND6 / D-loop region is excluded; Table 3). Thus, the divergence of the mitochondrial genomes of Channichthys rhinoceratus and C. rugosus is consistent with the existence of a single species within the genus Channichthys (Eastman & Eakin, 2021). If this result should be confirmed by further molecular data, Channichthys rugosus may need to be synonymized with C. rhinoceratus .…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…2) differ by 421–540 substitutions and 25–34 indels (253–272 substitutions and 6–11 indels when the ND6 / D-loop region is excluded; Table 3). Thus, the divergence of the mitochondrial genomes of Channichthys rhinoceratus and C. rugosus is consistent with the existence of a single species within the genus Channichthys (Eastman & Eakin, 2021). If this result should be confirmed by further molecular data, Channichthys rugosus may need to be synonymized with C. rhinoceratus .…”
Section: Discussionsupporting
confidence: 70%
“…In most cases, these species were described on the basis of few specimens only. To address a felt demand for a "complete overhaul" (Duhamel, Gasco, & Davaine, 2005;Eastman & Eakin, 2021) of the systematics of the genus Channichthys, Nikolaeva and Balushkin began a series of investigations based on comprehensive comparisons of specimens in the collections of the Zoological Institute of the Russian Academy of Sciences in Saint Petersburg, the Ukranian National Museum of Natural History in Kyiv, and the British Natural History Museum in London. Their analyses indicated that the duplicate gill rakers observed in C. rhinoceratus, C. panticapaei, C. bospori, and C. irinae, but also in more distantly related icefishes, are a rather labile character (Balushkin & Nikolaeva, 2015), leading them to suggest the synonymization of the latter three Channichthys species (Nikolaeva, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Trematomus Boulenger, 1902, includes fifteen benthic or epibenthic species, from small to moderate size, which dominate the continental shelf regions of Antarctica (Eastman and Eakin 2021). Most of them are circum-Antarctic and almost exclusively distributed in the High-Antarctic Zone (Kock 1992).…”
Section: Introductionmentioning
confidence: 99%